Measurement of Telomeric DNA Content in Human Tissues - Jennifer E. Bryant; Kent G. Hutchings; Robert K. Moyzis; Jeffrey K. Griffith (BioTechniques)
Telomeres, nucleoprotein complexes at the ends of eukaryotic chromosomes, are 10–12 kbp in length in somatic cells, but as small as 1–2 kbp in rapidly growing cancer cells. Southern blot analysis is currently the standard method for the measurement of telomere length. However, accurate determinations are not possible when DNA is broken or scant. To avoid these problems, a slot blot assay that quantitates the relative content, instead of length, of telomere DNA was developed. The relative contents of telomere DNA determined by this slot blot assay were directly proportional to the relative lengths of telomere DNA determined in parallel by Southern blot analysis. Relative telomere DNA content could be measured in samples containing as little as 15 ng of total DNA. Relative telomere DNA content, but not length, also was unaffected by breakage of DNA into fragments 1 kbp or less in length.